2008
DOI: 10.1016/j.molbiopara.2008.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Fly transmission and mating of Trypanosoma brucei brucei strain 427

Abstract: Like yeast, Trypanosoma brucei is a model organism and has a published genome sequence. Although T. b. brucei strain 427 is used for studies of trypanosome molecular biology, particularly antigenic variation, in many labs worldwide, this strain was not selected for the genome sequencing project as it is monomorphic and unable to complete development in the insect vector. Instead, the fly transmissible, mating competent strain TREU 927 was used for the genome project, but is not as easily grown or genetically m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 39 publications
6
29
0
Order By: Relevance
“…Our 427 strain, like many others (Peacock et al, 2008), has lost the ability to differentiate efficiently into PF. PF were grown in SDM79 with 15% fetal calf serum and BF cell were grown in HMI-9 with 10% fetal calf serum media.…”
Section: Methodsmentioning
confidence: 59%
“…Our 427 strain, like many others (Peacock et al, 2008), has lost the ability to differentiate efficiently into PF. PF were grown in SDM79 with 15% fetal calf serum and BF cell were grown in HMI-9 with 10% fetal calf serum media.…”
Section: Methodsmentioning
confidence: 59%
“…34 c Bernhard et al . 56 reported that STIB 900-P contained a wild-type TbAT1 gene; later analysis revealed that in fact the TbAT1 open reading frame contains one coding mutation (G1288C, leading to Gly 430  → Arg).…”
Section: Resultsmentioning
confidence: 99%
“…Tsetse flies were collected using biconical traps [43] during field expeditions between 2009 and 2012 from 49 sites. Sampling details are summarized in Figure 1, Table 1 and Supplementary Material.…”
Section: Methodsmentioning
confidence: 99%